A transient luminal chitinous matrix is required to model epithelial tube diameter in the Drosophila trachea. - Tonning, A.; Hemphala, J.; Tang, E.; Nannmark, U.; Samakovlis, C.; Uv, A. (Developmental Cell, 2005)
Epithelial tubes are found in many vital organs and require uniform and correct tube diameters for optimal function. Tube size depends on apical membrane growth and subapical cytoskeletal reorganization, but the cues that coordinate these events to ensure functional tube shape remain elusive. We find that epithelial tubes in the Drosophila trachea require luminal chitin polysaccharides to attain the correct diameter. Tracheal chitin forms a broad transient filament within the tubes during the restricted period of expansion. Loss of chitin causes tubular constrictions and cysts associated with irregular subapical cytoskeletal organization, without affecting epithelial integrity and polarity. Analysis of previously identified tube expansion mutants in genes encoding septate junction proteins further suggests that septate junction components may function in tubulogenesis through their role in luminal matrix assembly. We propose that the transient luminal protein/polysaccharide matrix is sensed by the epithelial cells and coordinates cytoskeletal organization to ensure uniform lumen diameter.